Childhood overweight/obesity and social inequality in peri-urban regions of Taipei - Chang, Shu Huei; Zhang, Yong; Lin, Cheng Te; Kao, Chung Lan; Lim, Boon Hooi; Hung, Ta Cheng; Tseng, Ching Yu; Kuo, Chia Hua (Elsevier, 2018)
A cross-sectional analysis of 33,942 schoolchildren at 6th grade (peri-urban New Taipei, N = 25,028; urban Taipei, N = 8914), representing >50% of children population of the age in Taipei metropolitan area, was examined for the disparity in overweight/obesity prevalence between urban and expanding peri-urban regions. Overweight/obese prevalence of schoolchildren at the age level is 30.4%. Peri-urban schoolchildren had higher overweight/obesity prevalence than urban peers (Girls: 26.0% vs 20.6%, P < 0.001; Boys: 37.1% vs 33.8%, P < 0.001). Children in both regions spent substantially more time on homework/reading than television viewing and computer use. Peri-urban children spent less time on homework/reading and more time on television and computer use than their urban counterparts (P < 0.001). Children with parental education category at “No College” were 54.8% in peri-urban area against 24.8% in urban area (P < 0.001). They were 1.0 cm shorter in height and ∼1.0 kg heavier in weight, and spent less time on homework/reading than those at “College” (P < 0.001). This is the first report presents a disparity in childhood overweight/obesity prevalence between peri-urban and urban places. Public efforts are needed to solve the childhood overweight/obesity problem secondary to social inequality in places at developing stages during urbanization.